2010
DOI: 10.1007/7854_2010_82
|View full text |Cite
|
Sign up to set email alerts
|

Cognitions and Emotions in Eating Disorders

Abstract: The cognitive model of eating disorders (EDs) states that the processing of external and internal stimuli might be biased in mental disorders. These biases, or cognitive errors, systematically distort the individual's experiences and, in that way, maintains the eating disorder. This chapter presents an updated literature review of experimental studies investigating these cognitive biases. Results indicate that ED patients show biases in attention, interpretation, and memory when it comes to the processing of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…The disorder is exceptionally difficult to treat, though treatment studies are scarce (Bulik, 2014). A series of cross-sectional studies show deviant neurobiological brain responses which led diverse experts to argue that AN is a neurobiological disorder (see e.g., Adan & Kaye, 2011;Bulik, 2014;Ehrlich, Geisler, Ritschel, King, Seidel, Bohm et al, 2015;Klump et al, 2009;O'Hara, Campbell, & Schmidt, 2015;Monteleone et al, 2016;Park, Godier, & Cowdrey, 2014;Treasure et al, 2010). They stress the abnormal functioning of central reward systems in AN and state that this deregulated reward processing is central to the development of AN.…”
Section: Restriction Of Intake and Food Rewardmentioning
confidence: 99%
“…The disorder is exceptionally difficult to treat, though treatment studies are scarce (Bulik, 2014). A series of cross-sectional studies show deviant neurobiological brain responses which led diverse experts to argue that AN is a neurobiological disorder (see e.g., Adan & Kaye, 2011;Bulik, 2014;Ehrlich, Geisler, Ritschel, King, Seidel, Bohm et al, 2015;Klump et al, 2009;O'Hara, Campbell, & Schmidt, 2015;Monteleone et al, 2016;Park, Godier, & Cowdrey, 2014;Treasure et al, 2010). They stress the abnormal functioning of central reward systems in AN and state that this deregulated reward processing is central to the development of AN.…”
Section: Restriction Of Intake and Food Rewardmentioning
confidence: 99%
“…Set shifting is the ability to change quickly one's cognitive set or frame of reference in order to meet changing current and situational demands (Miyake et al, 2000). A behavioral manifestation of poor setshifting includes cognitive inflexibility or a rigid tendency to approach problems repeatedly in the same fashion, perhaps even when the approach no longer leads to desired goals (this has also been described as an inability to approach problems abstractly; Siep et al, 2011). ED patients with AN and BN have shown setshifting deficits in their approach to eating, body image, and/or a general selfconcept and goal setting strategy (Roberts et al, 2007;Tchanturia et al, 2004Tchanturia et al, , 2012.…”
Section: The Role Of Executive Functioning In Disordered Eatingmentioning
confidence: 99%
“…Anorexia nervosa (AN) is a severe psychiatric disorder, for which a multifactorial etiology and maintenance including biological, socio‐cultural and psychological factors is assumed (Herpertz‐Dahlmann & Dahmen, 2019; Munro et al., 2017). According to the cognitive model of eating disorders (ED) biased processing of internal and external disorder‐relevant stimuli, for example, body or food images, is a relevant part of the etiology and maintenance of EDs (Siep et al., 2011). Former studies identified this altered processing of stimuli in terms of an attentional bias (AB) (Siep et al., 2011; Williamson et al., 2004).…”
Section: Introductionmentioning
confidence: 99%